Innovative immunotherapies and emerging treatments in type 1 diabetes management - Malek Zarei; Mohammad Abbas Sheikholeslami; Masoud Mozaffari; Yassar Mortada (Diabetes Epidemiology and Management)
Type 1 diabetes mellitus (T1D) is a chronic autoimmune disease characterized by the selective destruction of pancreatic insulin-producing beta cells, primarily mediated by CD4+ and CD8+ T cells. This review comprehensively examines the latest advances in immunotherapeutic approaches to T1D, categorizing current strategies into four main groups: antigen-independent therapies, antigen-dependent therapies, beta cell therapies, and stem cell therapies. Antigen-independent strategies, such as antibody-based therapies (e.g., Abatacept and Teplizumab) and cytokine inhibitors (e.g., Anakinra and Etanercept), have shown potential in preserving beta cell function by modulating immune responses. Antigen-dependent strategies focus on inducing immune tolerance to specific beta cell antigens, with mixed results from clinical trials involving autoantigen vaccines like GAD65. Beta cell therapies, including islet transplantation, offer promising outcomes but face challenges related to immunosuppression and donor availability. Stem cell therapies, particularly using mesenchymal stem cells (MSCs) and autologous hematopoietic stem cells (HSCs), demonstrate potential in immune modulation and beta cell regeneration. Novel approaches, such as Chimeric Antigen Receptor (CAR)–Tregs therapy and JAK-STAT pathway inhibition, represent exciting areas of ongoing research. This comprehensive overview underscores the necessity of personalized therapeutic approaches and continued research to optimize existing therapies and explore new targets, ultimately aiming to improve outcomes and achieve a potential cure for T1D.